The Integration of Bugis Cultural Values and Islamic Teachings in Digital Media - Mahanani, Prima Ayu Rizqi; Syafuddin, Khairul (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2024)
This study aims to explore how Ustaz Das'ad Latif utilises YouTube to integrate Bugis cultural values with Islamic teachings, focusing on marriage. The research employs a multimodal discourse analysis framework to examine the ideational, interpersonal, and textual functions in Ustaz Das'ad Latif's YouTube lectures. The study reveals that Siri’ culture, central to Bugis identity, is intertwined with Islamic values, particularly regarding gender roles, honour, and family dynamics. Digital media serves as an effective tool for both preserving and reshaping these cultural values. The findings suggest that digital platforms like YouTube can serve as vital spaces for the global dissemination and transformation of local traditions, offering new interpretations that resonate across cultural boundaries. This research provides novel insights into the role of digital media in preserving local religious traditions while adapting them for broader audiences, contributing to the growing literature on religion, culture, and technology.